2021
DOI: 10.3390/ijfs9040071
|View full text |Cite
|
Sign up to set email alerts
|

Has the EU-ETS Financed the Energy Transition of the Italian Power System?

Abstract: This paper focuses on the relationship between the European Union Emission Trading System allowances’ prices and the Italian electricity price, aiming at assessing whether such a mechanism has been a driver for the decarbonization of the power sector. To this aim, we calculate the long-run relationships between energy prices, natural gas prices and allowances’ prices, through a VECM model, distinguishing between peak and off-peak prices. The analysis is carried out for the third phase of the EU-ETS, which star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…When exploring the relationship between the carbon market and the energy generation industry, it is also necessary to consider the relationship between carbon prices and electricity prices. Koch et al (2013) argue that electricity prices have a positive impact on carbon prices, while Caporin et al (2021) found in their study of the Italian carbon market that an increase in 1 euro carbon price is accompanied by an increase in 7 euro cents electricity prices. However, research has shown that there is no strong causal relationship between carbon prices and electricity prices.…”
Section: Discussion On the Heterogeneity Of The Carbon Market In The ...mentioning
confidence: 99%
See 1 more Smart Citation
“…When exploring the relationship between the carbon market and the energy generation industry, it is also necessary to consider the relationship between carbon prices and electricity prices. Koch et al (2013) argue that electricity prices have a positive impact on carbon prices, while Caporin et al (2021) found in their study of the Italian carbon market that an increase in 1 euro carbon price is accompanied by an increase in 7 euro cents electricity prices. However, research has shown that there is no strong causal relationship between carbon prices and electricity prices.…”
Section: Discussion On the Heterogeneity Of The Carbon Market In The ...mentioning
confidence: 99%
“…The implementation of carbon emission trading markets will invisibly increase the energy costs of carbon emissions, not only affecting the production costs of industrial producers, but also guiding consumers to make rational choices and stimulating the demand for low-carbon energy. Therefore, there is a two-way linkage relationship between the carbon market and the energy market (Caporin et al, 2021;Hammoudeh et al, 2014). This is also the "linkage effect" theory proposed by Hirschman (1958), where the impact of fossil energy prices on carbon prices can be divided into two paths: income effect and substitution effect.…”
Section: The Relationship Between Carbon Prices and Energy Pricesmentioning
confidence: 94%
“…There exist a large literature on the estimate of electricity costs pass-through, that we cannot review here. See for instanceCaporin et al (2021) and references therein.13 Similarly, we do not consider the lag-time that usually exists between the awarding of the premium and the effective delivery of capacity, and similarly assume that new investments occur instantaneously.…”
mentioning
confidence: 99%